SARS-CoV-2 convalescent plasma for the controlled clinical trial “COVIC-19”: experience from collection of very high-titer plasma from superimmunized individuals - Hoffmann, Simone; Seidel, Alina; Ludwig, Carolin; Vieweg, Christiane; Müller, Rebecca; Hofmann, Henrike; Jahrsdörfer, Bernd; Wuchter, Patrick; Klüter, Harald; Schmidt, Michael; Johnsen, Matthias; Burkhardt, Thomas; et al. (Transfusion, 2025)
Background COVID-19 convalescent plasma (CCP) is a treatment option for COVID-19. Understanding of donor and product characteristics is important for optimization of CCP therapy. We report the experience of collection of very high-titer CCP for the trial “A randomized open-label trial of early, very high-titer convalescent plasma therapy in clinically vulnerable individuals with mild COVID-19” (COVIC-19) (NCT05271929). Study Design and Methods Individuals who had recovered from COVID-19 and had ≥1 dose of a SARS-CoV-2 vaccine were recruited as donors for CCP. Anti-SARS-CoV-2 antibodies were measured by ELISA, and neutralization capacity against SARS-CoV-2 variants was assessed in surrogate and pseudovirus-neutralization assays. Correlation of antibody titers with donor characteristics and antibody kinetics was analyzed. Results We recruited 688 potential donors. 41.4% of individuals had antibody concentrations of ≥4000 BAU/ml (anti-SARS-CoV-2 IgG ELISA [QuantiVac]). Concentrations did not significantly differ by sex or ABO type, but were higher among those who had received at least three vaccinations. Highest titers were observed in those with a breakthrough infection after two vaccinations, followed by a booster (median 5374 BAU/mL) or breakthrough infection after the 3rd or 4th vaccination (median 3846 BAU/mL). Ultimately, 172 eligible individuals donated CCP with a median concentration of 6858 BAU/mL (range 4015-22,923 BAU/mL). Discussion We demonstrate the feasibility of the collection of very high-titer CCP products under a harmonized protocol for a randomized clinical trial, but it requires substantial donor selection, appropriate antibody assays, rapid succession of screening, and apheresis to take advantage of the short period of very high antibody concentrations.
Erstmals veröffentlicht: 12. September 2025
Gesehen am 16.10.2025